2018
DOI: 10.1159/000486330
|View full text |Cite
|
Sign up to set email alerts
|

Immunooncology in Breast Cancer: Active and Passive Vaccination Strategies

Abstract: Immunotherapies are set to become part of the therapeutic repertoire for breast cancer in the near future. Active vaccination is a promising strategy, especially in tumors that have a specific tumor-associated antigen. Although cellular immunotherapies have not yet shown efficacy, new technologies are on the way to improve this approach. Given the recent Food and Drug Administration approval of chimeric antigen receptor (CAR) T cells for leukemia, it is only a question of time before solid tumors will follow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the last few years, immunotherapy emerged as a promising therapeutic approach for different tumors, especially in those having a specific tumor-associated antigen including breast cancer. However, some breast cancer patients did not respond to cellular or other immunotherapy including monoclonal antibodies, checkpoint inhibitors, or oncolytic virus therapy, and consequently, still there is an increased incidence of relapse and mortality [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, immunotherapy emerged as a promising therapeutic approach for different tumors, especially in those having a specific tumor-associated antigen including breast cancer. However, some breast cancer patients did not respond to cellular or other immunotherapy including monoclonal antibodies, checkpoint inhibitors, or oncolytic virus therapy, and consequently, still there is an increased incidence of relapse and mortality [27].…”
Section: Discussionmentioning
confidence: 99%
“…There are many trials performed to develop an efficient active DCs-based immunotherapy for breast cancer patients, however, their clinical benefit is still not promising. The main obstacles facing these trials are difficulties in producing broad and robust immune responses, as well as overcoming immune escape mechanisms [4,27]. Thus, in the present study, we tried to overcome these major obstacles by mixing the peripheral blood immature DCs, and naïve T cells together with TIDCs, and TILs during interaction with BCCs.…”
Section: Discussionmentioning
confidence: 99%
“…There are different types of vaccines depending on the type of antigen. The most studied are those formulated with tumor-associated antigen (TAA) peptides [ 48 ], but others such as tumor protein- or carbohydrate-associated antigens, and antigens based on DNA and DCs are also being studied to stimulate both innate and adaptive antitumor immunities [ 39 , 49 , 50 , 51 ].…”
Section: Immunotherapy In Breast Cancermentioning
confidence: 99%
“…Although this vaccine is able to induce a specific T-cell response, the clinical outcomes achieved in this study are still unsatisfactory. 14 The largest phase III clinical trial using STnkeyhole limpet hemocyanin (KLH) vaccine (Theratope ®; Biomira, Inc., Edmonton, Canada), a conjugated STn synthetic tumor antigen in combination with an adjuvant, in 1028 patients with metastatic breast cancer found that this vaccine was well tolerated with good and able to stimulate the formation of antibodies against MUC-1 antigen, but did not provide benefits in patient outcome and survival. 15 Preclinical studies using tumor cells with expression of MUC-1 protein or peptide antigen concluded that MUC-1 can induce a humoral immune response without inducing a cellular response.…”
Section: Mucin-1 Vaccinementioning
confidence: 99%